Enhancing the sensory attributes and antioxidant properties of snus by mixing it with tea - Wang, Y. (2024)
In the present work, we investigated the chemical and volatile compositions of three tea-containing snus samples, after which their acceptability on the aromatic and taste coordination was evaluated by a professional panel. Results showed that the tea-containing snus samples exhibited better acceptability on the aroma and taste coordination profiles. Dahongpao tea (DT)-containing snus (DT-snus) exhibited the best acceptability of aromatic coordination, whereas the most favourable taste coordination was exhibited by Keemun black tea (KBT)-containing snus (KBT-snus). The antioxidant activity determined by the DPPH and ABTS assays revealed that Lu’an Guapian tea (LGT)-containing snus (LGT-snus) exhibited the highest free-radical scavenging ability. LGT-snus was also found to have the highest content of total polyphenols, amino acids, and caffeine. The highest levels of total flavonoids and soluble sugars were found in DT-snus and KBT-snus, respectively. There were 88, 68, and 74 volatiles found in DT-snus, LGT-snus, and KBT-snus, respectively, among which, nitrogenous compounds constituted the major category. High levels of nicotine, megastigmatrienone, neophytadiene, nicotyrine, and cotinine, which are the major volatiles in snus, were detected in the tea-containing snus samples. The mixing of tea introduced the flavour profiles of the volatiles present in the original tea into the tea-containing snus samples. Benzaldehyde, β-ionone, hexanoic acid, 3-(Z)-hexenyl ester, pyrazines, and nerolidol from LGT; furfural, benzeneethanol, nerolidol, linalool, and cedrol from DT; and nonanal, geraniol, cis-jasmone, benzenemethanol, and methyl salicylate from KBT were found in high concentrations in the corresponding tea-containing snus samples.